Social Media Marketing Training for Merchants at Ngarsopuro Night Market Solo - Sari, Puspa Novita; Andraeny, Dita (Institut Teknologi Nasional, Bandung, 2025)
The Ngarsopuro Night Market Solo Merchants Association is currently facing competition challenges from online traders as well as a lack of technological knowledge. These obstacles make it difficult for merchants to compete. To address these issues, training and mentoring activities on the use of social media were conducted in October 2024, attended by 50 association members. The method applied was the PAR (Participatory Action Research) method.The activity results showed an increase in the engagement rate on participants’ accounts. The engagement rate, which was previously below 1% (low engagement), significantly increased to more than 3% (high engagement). This increase demonstrates that the program effectively improved customer engagement.Recommendations for the program’s sustainability include conducting advanced training and initiating the formation of a digital community for Ngarsopuro Night Market Solo Merchants. It is hoped that this activities can continue and provide long-term benefits for the Ngarsopuro Night Market Solo Merchants Association.